Emergency remote teaching: virtualization of life and precarious teaching work - Chaves de Farias, Ricardo; Mota Pereira da Silva, Denise (Geografares, 2021)
The Covid-19 pandemic surprised the world, caused changes in ways of life, in labor practices and exposed the inequalities of the current technical-scientific-informational period. In the educational system, teachers needed to reinvent themselves so that the closure of schools would not be so harmful to the teaching-learning process. In this context, the article analyzes the role of Geography teachers during the Covid-19 pandemic based on a brief theoretical discussion on the history of distance education in Brazil, teacher training and teaching knowledge, in order to learn about working conditions of these professionals throughout social isolation. To this end, a questionnaire was applied to geography teachers working in basic education. The results showed difficulties, on the part of the research subjects, with the remote modality, denounced the negligence of the authorities responsible for Education and revealed the teachers’ concern in guaranteeing learning conditions for the students, at the same time that their homes became places of work.